Locating value
1 online resource (xv, 213 pages).
Keywords: "This book considers value at the root of our actions and 'decision-making': an ever-present, yet little discussed or interrogated aspect of everyday life, yet increasingly present in public policy. It examines value as it is theorised, practiced, and critiqued from varied disciplinary perspectives. Locating Value: Theory, Application and Critique examines how value features in contemporary society - how it is operationalized, endorsed, and contested. The 15 chapters represent a much-needed diverse and vibrant geographical engagement with value that reflects value's conceptual flexibility. They lay value's eclectic epistemic foundations; examine value's 'roll-out' and legitimation across a range of policy fields; and outline its challenge, with international examples of where and how value touches down: from forest conservation in Indonesia, protected area management in arctic Svalbard, heritage planning in East Taiwan, local food networks in Canada and the UK; a re-developed Norwegian airport site, a Chicago market, urban development in Jiangsu Province China, a state park in the Californian mountains; to certification schemes for biodiversity offsetting in the UK and protection of the international night sky. The book will be of interest to human geographers, political ecologists, heritage scholars and practitioners, planners and those working in public policy, as well as anyone with an interest in how valuation processes work"--